Analysis of oil spills from ships and their management in Perú - Ramírez Caján, Alfonso (2021)
This research presents the analysis of port and aquatic management in Peru, on the control and combat of pollution from oil spills from ships; based on a detailed review of the various environmental instruments and international organizations, which promote and promote the exchange of information and technology, to prevent and mitigate socio-environmental and economic risk at the local, national, and regional level, which may compromise its main water resources and aquatic biota. Likewise, the statistics of spills over time are shown, with a total of 922.74 m3 of hydrocarbons discharged, being the aquatic port area of Yurimaguas and Zorritos the one with the greatest impact, considering the response capacity and preparation and the availability of equipment and means available to face these events.